Rock star ebook - Holm, Jennifer L. (Babymouse, 2012)
Meet Babymouse—the spunky mouse beloved by young readers for more than a decade! Babymouse plans to be the star in the school concert but she needs to hit all the right notes. Can she and her flute shine in the spotlight? This groundbreaking young graphic novel series, full of humor and fun, is a bestseller that’s sold more than three million copies! "Move over, Superman, here comes Babymouse!"— The Chicago Sun-Times Move over Mozart! Babymouse has music in her soul...but sadly, n ot in her flute. Will Babymouse ever hit the right note? Will she be the star of the school concert, or is her musical career all washed up before it's even started? Find out in Rock Star , the sensational 4th book in the Babymouse graphic novel series! DON'T MISS The BIG Adventures of Babymouse: Once Upon a Messy Whisker , the newest, brightest, and BIGGER THAN EVER graphic novel from BABYMOUSE!